A Model to Increase Community Participation in Waste Reduction in the Naimata and Penfui Sub-districts - Enni Rosida Sinaga; Albina Bare Telan; Siprianus Singga; Yusmidiarti (Jurnal Penelitian Pendidikan IPA, 2025)
Community participation played an essential role in reducing household waste in Kupang City, where waste management had remained poor and piles of garbage were common along the streets. This study aimed to enhance community involvement in managing and reducing household waste. A descriptive method was applied, involving 72 households from housing complexes in Naimata and Penfui villages. Data was collected through interviews, observations, and community-based interventions such as Focus Group Discussions (FGD), education, and assistance from local leaders. The treatment significantly improved community participation: households with good waste management practices increased from 8 to 52, while those with poor management decreased from 64 to 20. The number of households utilizing waste rose from 22 to 62, and those processing organic waste into compost increased from 7 to 68. Organic waste generation dropped from 72 liters/day to 13 liters/day, and inorganic waste from 239 to 215 liters/day. The study concluded that community-based education and support effectively enhanced waste reduction behaviors, highlighting the need for continued government and community collaboration to sustain these practices.